Enabling the Visible Hand - Ian Keay; Marina Adshade (Queen's University, Department of Economics, 2006)
In this paper we use data from more than 2,500 industry-years, reported by the Ohio Division of Labor Statistics, to track changes in employment and weekly wages among male and female production workers and clerical workers between 1914-1937. We find that among Ohio's manufacturing establishments female employment and real wages were rising throughout this period, particularly within clerical occupations. Increases in women's share of the total manufacturing workforce were nearly monotonic between 1914-1937, while after having been, at best, stagnant until the mid- 1920s, women's relative wages increased through the last half of the 1920s and into the 1930s. After matching our employment and wage data with information from the Census of Manufactures for the state of Ohio, we estimate translog production functions which indicate that Ohio manufacturers were adopting new organizational structures and technologies that were biased in favor of female clerical labor. This non-neutrality in technological and organizational change (like the employment and wage patterns) was driven primarily by larger firms that had relatively complex production processes. A simple counterfactual exercise indicates that the adoption of non-neutral technological and organizational change over this period can explain much of the observed increase in demand and remuneration for educated female manufacturing workers. This conclusion emphasizes the role women played channeling early twentieth century organizational and technological change, in effect enabling Chandler's "visible hand".
Keywords: N12; N32; 330; US manufacturing; Female labor force participation; Technological change